Gweru hospital telemedicine app - Muzavazi, Perrence Munyaradzi (Midlands State University, 2018)
In line with National Development Priorities and the UN Millennium Development Goals as documented in the Zim-Asset blueprint under the Social Services and Poverty Eradication cluster, the health care system is not greatly benefiting from the wide spread use of ICT solutions countrywide. Every process in the medical sector requires the patient and the health practitioner to be in the same room regardless of the nature of visit. Thus unnecessary meetings like consultations, education, and data sharing even check-ups are not benefiting from the virtualisation that technology brings. Gweru Hospital Telemedicine is an android application used by patient to interact with remote doctors to send and receive data about prescriptions, consultations, referrals, bills. This project is aimed to provide remote communication and collaboration between patient and health care workers. The platform is to be modularised into consultation, education and data transfer components to provide a minimum viable product for proof of concept. A thorough feasibility study of the system was weighed to enable assessment of the practicality and application of the system and enabled the determination of the system’s viability. The inputs, processes and outputs of the system were designed as well as the flow of data accompanied with entity relationships and databases. As designing was done, proper verification and validation for the system follows so as to come up with a system with data integrity. Finally, after the system was designed successfully, it was tested to see if it meets the user expectations. Vulnerability scanner tools were used to identify development errors, configuration faults and transaction sequence faults. Java, XML, SQLite and the Firebase I/O were used for the design and development process.